The Effectiveness of Student Worksheets (LKS) in Enhancing Fiqh Learning Outcomes for Seventh-Grade Students at MTs Barakatul Walidain - Ayatullah (Journal of Education, Teaching, and Learning, 2024)
This study explores the effectiveness of Student Worksheets (LKS) in improving Fiqh learning outcomes among seventh-grade students at MTs Barakatul Walidain. Using a quantitative research design, the research assessed the impact of LKS on students' academic performance and understanding. The study employed pre-tests, post-tests, and questionnaires as data collection tools. A sample of 30 students was selected through simple random sampling. Pre-tests were conducted to establish baseline knowledge, followed by the integration of LKS into classroom activities for six weeks. Post-tests and feedback from students and teachers were subsequently collected. Data analysis employed descriptive statistics and a paired sample t-test, revealing a significant improvement in student performance after LKS implementation (t = 8.76, p < 0.001). Results indicated that LKS facilitated a better understanding of Fiqh concepts, with students reporting high levels of clarity (85%), usability (80%), and engagement (78%). Teachers observed enhanced classroom interaction and teaching efficiency. Thematic analysis further emphasized the role of LKS in fostering comprehension and encouraging interactive learning environments. However, challenges such as time constraints and limited resources were noted. These findings underline the potential of LKS as a practical and impactful instructional tool for improving educational outcomes in Fiqh and similar subjects. Future studies could explore strategies to address implementation challenges and expand LKS use across broader educational contexts.